MAHAR TANAH DALAM PEMAHAMAN MASYARAKAT BUGIS BONE DAN KEDUDUKANNYA DALAM ISLAM - RUSMAN, RUSMAN; KANANG, ABD. RAHMAN (STIT Sunan Giri Bima, 2020)
This research is a descriptive qualitative research, aimed at knowing and examine dowry in the form of a plot of land at the Bugis community wedding Bone is based on the perspective of Islamic law and the Basic Laws Agraria. This research will reveal the understanding of the Bugis Bone community regarding land dowry, its position is like the legal certainty of the two perspectives the. The location of this research Bone district South Sulawesi. Data source taken from observations or direct observations of local community leaders who considered to understand and make a plot of land as a dowry marriage. Data collection methods used are observation, interview, and documentation. The instrument used in the form of researchers as instruments headline, observation guide, interview guide, and check list of documents and tools other supporters such as cameras and stationery. Data processing techniques began data collection, data reduction, organizing data, and verifying data. Results research is to make a plot of land as a dowry in traditional marriages Bugis Bone is a tradition that has long been practiced. Land is an object or goods that are best made dowry because they contain philosophical values in line with human life. There are two forms of dowry ownership, namely, possessing only part of it is enjoying the results but not mastering the object of the land fully, the second is only a mere symbol. Mentioned in the contract but the wife does not know the reality of the object of the land. Land acquisition as a right property with a dowry is permissible in Islamic law but does not have certainty law in the perspective of laws and regulations.